Pengaruh Komunikasi Visual Berbasis Artificial Intelligence terhadap Kinerja UMKM Kuliner di Kota Serang: Mediasi Customer Engagement - Eko Agung Sugiyarto; Laely Rizki Maulida; Ismiyati Hanum; Zahra Inesya Putri; Kayla Ghayata Amalia Putri; Nesyla Damayanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Digital transformation has driven changes in Micro, Small, and Medium Enterprises (MSMEs) marketing strategies through the utilization of Artificial Intelligence (AI) technology, particularly in the development of visual communication on social media. AI technology enables business owners to generate more creative, personalized content tailored to audience characteristics, thereby potentially enhancing customer engagement and business performance. This study aims to analyze the effect of Artificial Intelligence-based visual communication on customer engagement, examine the effect of customer engagement on MSME performance, and test the mediating role of customer engagement in this relationship. The research employs a quantitative approach with an explanatory research design. Data were collected through observation, brief interviews, and questionnaires distributed to 383 culinary and fashion MSME owners in Serang City, selected using a purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The results indicate that AI-based visual communication has a positive and significant effect on customer engagement (β=0.788; p<0.001) and MSME performance (β=0.325; p<0.001). Furthermore, customer engagement is proven to have a positive effect on MSME performance (β=0.614; p<0.001) and acts as a partial mediator. This study concludes that the implementation of AI-based visual communication enhances digital marketing effectiveness and contributes to improving MSME performance through stronger customer engagement. These findings serve as practical recommendations for MSME owners in Serang City to optimize the use of AI as a competitive strategy in the digital economy era